2004
DOI: 10.1002/crat.200310230
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectrical properties of In1‐xGaxAs and InAs crystals irradiated with fast electrons

Abstract: The thermoelectric power in In 1-x Ga x As (x=0,01;0,04) solid solutions and InAs crystals irradiated with fast electrons by the energy of 6 MeV and dose of 10 16 -2x10 17 el/cm -2 on the interval 80-400K have been investigated. It is revealed that in the all crystals the value of the thermoelectric power is decreased under irradiation that resulted from the growth of the free electron concentration to form radiation induced defects of the donor type. It has been determined that in the initial InAs after irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The relative error of alloy composition determination was not higher than 2%, and the error of electro physical parameter determination runs between 5% and 7%. The qualitative analysis of the solid solution studies has shown sufficiently microhomogencity (up to 1µm) throughout the sample surface [2][3][4]7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative error of alloy composition determination was not higher than 2%, and the error of electro physical parameter determination runs between 5% and 7%. The qualitative analysis of the solid solution studies has shown sufficiently microhomogencity (up to 1µm) throughout the sample surface [2][3][4]7].…”
Section: Methodsmentioning
confidence: 99%
“…The existence of the chemical disorder in In 1-x Ga x As is apparent in the transport properties as an additional scattering mechanism of the current carriers [1][2][3][4][5][6][7]. The chemical disorder may generate local fluctuations of molar fraction, which cause a local change of the band-edge energy and the effective mass of the current carriers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%